DIPLOMASI KEBUDAYAAN INDONESIA DALAM MEMPROMOSIKAN PARIWISATA INDONESIA DI SELANDIA BARU TAHUN 2014-2019 - Alfian Rizki Saputra; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research analyzes the form of cultural diplomacy by Indonesia to promoting Indonesian tourism in New Zealand in 2014-2019. Indonesia has begun to increase tourism cooperation and doing cultural diplomacy activities in New Zealand to increase the number of New Zealand tourist visits.This research uses a pluralism perspective where policies can be from different actors. This study was also analyzed using the theory of cultural diplomacy. The methodology used in this research is a qualitative method with a descriptive model.. The data obtained by doing literature study and documentation study that which consist of articles, journals, and website.This research shows the results of Indonesia's cultural diplomacy against New Zealand in 2014-2019. Cultural diplomacy carried out by Indonesia uses the form of diplomacy in the form of exhibitions, competitions, negotiations, student exchanges, and conferences. The forms of diplomacy that have been carried out by Indonesia have an impact on increasing the level of New Zealand tourist visits to Indonesia, as well as increasing cooperation between Indonesia and New Zealand in the tourism sector.Keywords: Cultural Diplomacy, Wonderful Indonesia, New Zealand.